SMARCA4-deficient NSCLC treated with first-line tislelizumab and fruquintinib achieved remarkable tumor regression: case report and literature review - Dong, Jie; Zhang, Jinli; Pan, Hongming; Wang, Chongwei; Sheng, Jin (Frontiers in Immunology, 2025)
SMARCA4-deficient non-small cell lung cancer (SMARCA4-dNSCLC) typically lacks target-driven gene alterations and are primarily resistant to cytotoxic drugs. There is currently no standard treatment, especially for those who are unwilling or unable to receive chemotherapy. This case reported that chemotherapy-free strategy with tislelizumab and fruquintinib was utilized as a first-line treatment for a patient with SMARCA4-deficient NSCLC, and the patient achieved remarkable partial remission and lasted more than two years of disease control without severe adverse events.